2008
DOI: 10.1177/135965350901400413
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate and risk factors for loss to follow-up in HIV-infected patients from five French clinical centres in Northern France – January 1997 to December 2006

Abstract: Background Our goal was to determine the incidence rate and risk factors for loss to follow-up (LTFU) of HIV-infected patients in Northern France. Methods We estimated the incidence rate of LTFU in 1,007 HIV-infected patients under care from January 1997 to December 2006. We then investigated potential risk factors for LTFU at inclusion and during follow-up. Results The incidence of LTFU was estimated to be 3.5 per 100 person-years. Risk factors for LTFU at enrolment in a multivariate Cox model were age <30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A study in South Africa reported an incidence rate of LTFU of 10.3 per 100 person-years in the 1st year on ART and increased to 40.5 per 100 person-years in the 8th year of ART [ 15 ]. This contrasts with LTFU incidence rates reported in developed countries at 4.2 per 100 person-years reported among ART experienced participants by the AIDS Clinical Trials Group (ACTG) Longitudinal Linked Randomized Trials (ALLRT) prospective cohort of 4630 participants [ 16 ] and, 3.5 per 100 person years among 1007 patients in France between 1997 to 2006 [ 17 ].…”
Section: Introductionmentioning
confidence: 68%
“…A study in South Africa reported an incidence rate of LTFU of 10.3 per 100 person-years in the 1st year on ART and increased to 40.5 per 100 person-years in the 8th year of ART [ 15 ]. This contrasts with LTFU incidence rates reported in developed countries at 4.2 per 100 person-years reported among ART experienced participants by the AIDS Clinical Trials Group (ACTG) Longitudinal Linked Randomized Trials (ALLRT) prospective cohort of 4630 participants [ 16 ] and, 3.5 per 100 person years among 1007 patients in France between 1997 to 2006 [ 17 ].…”
Section: Introductionmentioning
confidence: 68%
“…Death Ethiopia [17,18,31], this may be due to that the patients with the poor level of adherence for ART drug become interrupt the treatment schedule which leads to resisting to the virus. This treatment interruption make fail to suppress the viral load and become prone to poor treatment outcome like treatment failure, this leads the patient to lose hope for a good prognosis, and He/she prefers to lost from care after all the outcome turned to death [4,7].…”
Section: Discussionmentioning
confidence: 99%
“…The goals of ART are to lead and effectively suppress viral replication in order to prevent the development of HIV drug resistance, treatment failure, and lost follow-up. Adherence to ART and retention in HIV care program are critical for achieving optimal health outcomes in HIV patients [7,8]. Loss of followup from ART service has a pronounced negative impact on ART treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in different European countries have linked LTFU with younger age, people who inject drugs (PWID), having an immigration background, not being a man who has sex with men (MSM), having a shorter time since HIV diagnosis, and CD4+ cell counts <350 cells/μL [15–18]. In Spain, determinants of LTFU included younger age, less time in treatment, use of injecting drugs, unemployment, immigration, and being treated in a big hospital (>1000 patients in HIV care) [13].…”
Section: Introductionmentioning
confidence: 99%